Optimization of Wind Turbine Performance through Advanced Materials and Design - Animasaun, Akeem Babatunde; Adeniran, Adetayo Olaniyi; Udorah, Felix Nnamdi; Oluyemi, Israel Anuoluwapo (Optimality, 2025)
Improving wind turbine blade design and overall performance is essential; as a result, this study offers a thorough analysis of recent developments in advanced materials and aerodynamic optimization techniques. The escalating global demand for sustainable power necessitates maximizing the efficiency and sustainability of wind energy. Despite progress, challenges remain in optimizing energy capture, ensuring the structural integrity of increasingly larger turbines, and addressing environmental concerns. This review critically examines the potential of high-performance composites (such as CFRPs and bio-based alternatives), smart materials (including SMAs and self-healing polymers), and nanomaterials (for surface coatings) to improve blade performance, durability, and sustainability. Furthermore, it analyses the impact of innovative aerodynamic profiles (including bio-inspired designs), variable pitch and twist technologies, and load reduction strategies on energy efficiency. The study identifies key challenges and research gaps in the integrated application of advanced materials and aerodynamic design for next-generation wind turbines, emphasizing the need for cost-effective and scalable solutions alongside comprehensive Life Cycle Assessments (LCAs). By synthesizing current knowledge, this review highlights promising future research directions to achieve more efficient, sustainable, and economically viable wind energy solutions through the synergistic advancement of materials and design.